Science in the Soul: Selected Writings of a Passionate Rationalist - Gregory, Geoff (New Zealand Science Review, 2017)
As the century drew to a close, Richard Dawkins, the only scientist among invited lecturers to a BBC feature on ‘What will the 20th century leave to its heirs?’, bewailed the ‘hijacking by pseudoscience and bad science fiction [that] is a threat to our legitimate sense of wonder’ as are the ‘wacky ‘personalities’ ... performing funky tricks to show that science is fun, fun, fun’. He also considered that ‘the twentieth century ended with approximately the same level of supernatural credulity as the nineteenth, and rather more outright hostility to science’. This talk is one of forty-one of his essays, speeches, and articles produced over the last three decades and brought together in this anthology. <span style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 87.8587px; top: 403.078px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.899092);">cles <span style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 87.8587px; top: 423.078px; font-size: 16.6667px; font-family: sans-serif; transform: scaleX(0.900912);">produced over the last three decades and brought together in this anthology.